NQO1-dependent redox cycling of idebenone: effects on cellular redox potential and energy levels. - Roman H Haefeli (Public Library of Science (PLoS), 2011)
Short-chain quinones are described as potent antioxidants and in the case of idebenone have already been under clinical investigation for the treatment of neuromuscular disorders. Due to their analogy to coenzyme Q10 (CoQ10), a long-chain quinone, they are widely regarded as a substitute for CoQ10. However, apart from their antioxidant function, this provides no clear rationale for their use in disorders with normal CoQ10 levels. Using recombinant NAD(P)H:quinone oxidoreductase (NQO) enzymes, we observed that contrary to CoQ10 short-chain quinones such as idebenone are good substrates for both NQO1 and NQO2. Furthermore, the reduction of short-chain quinones by NQOs enabled an antimycin A-sensitive transfer of electrons from cytosolic NAD(P)H to the mitochondrial respiratory chain in both human hepatoma cells (HepG2) and freshly isolated mouse hepatocytes. Consistent with the substrate selectivity of NQOs, both idebenone and CoQ1, but not CoQ10, partially restored cellular ATP levels under conditions of impaired complex I function. The observed cytosolic-mitochondrial shuttling of idebenone and CoQ1 was also associated with reduced lactate production by cybrid cells from mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS) patients. Thus, the observed activities separate the effectiveness of short-chain quinones from the related long-chain CoQ10 and provide the rationale for the use of short-chain quinones such as idebenone for the treatment of mitochondrial disorders.